2020
DOI: 10.1186/s13000-020-01007-w
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of miR-186-5p for carotid artery stenosis and its predictive significance for future cerebral ischemic event

Abstract: Background MicroRNAs (miRNAs) serve as novel promising biomarkers for the diagnosis and prognosis of many human diseases. This study investigated the diagnostic value of miR-186-5p for asymptomatic carotid artery stenosis (CAS), and its predictive value for future cerebral ischemic events (CIEs). Methods Sixty-seven cases with asymptomatic CAS and 60 healthy individuals were recruited. Serum levels of miR-186-5p were tested by using qRT-PCR. Receiving–operator character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…In addition, functional miRNAs associated with disease progression are also deregulated in ACAS. For instance, miR-106b-5p ( 13 ) and miR-186-5p ( 22 ) have been indicated to be abnormal in ACAS and associated with ACAS progression. Yan et al ( 23 ) determined that the levels of serum miR-503-5p in patients with ACAS were significantly reduced compared with those in healthy individuals and that miR-503-5p was able to improve CAS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, functional miRNAs associated with disease progression are also deregulated in ACAS. For instance, miR-106b-5p ( 13 ) and miR-186-5p ( 22 ) have been indicated to be abnormal in ACAS and associated with ACAS progression. Yan et al ( 23 ) determined that the levels of serum miR-503-5p in patients with ACAS were significantly reduced compared with those in healthy individuals and that miR-503-5p was able to improve CAS.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Chen et al ( 14 ) reported that miR-92a may be a potential risk factor for the future onset of cerebrovascular events (including 20 cases of TIA and 8 cases of stroke; study cohort size, 122). A study by Lv et al ( 22 ) determined that miR-186-5p was able to predict the occurrence of future cerebral ischemic events (including 19 TIAs and 5 strokes; study cohort size, 67). Serum miR-106b-5p predicted the occurrence of cerebral ischemic events ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…The progression of carotid atherosclerosis is slow, and carotid stenosis may remain asymptomatic in many cases (2). However, symptomatic patients may present with transient or permanent contralateral neurologic deficits such as weakness or numbness.…”
Section: Introductionmentioning
confidence: 99%
“…As a small, highly conserved non-coding RNA molecule, microRNAs (miRNAs) can regulate the physiological and pathological processes of disease by inducing target mRNA degradation or blocking translation. 8 In recent years, many studies have shown that a variety of miRNAs are dysregulated in CAS, such as miR-330-5p, 9 miR-186-5p, 10 and miR-214, 11 suggesting that miRNAs have a greater potential regulatory role in CAS. Among the reported miRNAs, miRNA-28-5p attracted our attention.…”
Section: Introductionmentioning
confidence: 99%
“…CircCBFB promotes the occurrence of abdominal aortic aneurysms by influencing the apoptosis of VSMCs through miRNA-28-5p. 10 Besides, miR-28-5p affects the upregulation of the ABCA1-signaling pathway by regulating ERK2, thus affecting atherosclerosis. 12 Although miR-28-5p can affect common vascular disease, including abdominal aortic aneurysm and atherosclerosis, its effect on the pathogenesis of CAS and its VSMCs in CAS has not been reported.…”
Section: Introductionmentioning
confidence: 99%